Selection of bifenthrin resistance in cotton mealybug Phenacoccus solenopsis Tinsley (Homoptera: Pseudococcidae): Cross-resistance, realized heritability and possible resistance mechanism. (September 2016) - Mansoor, Muhammad Mudassir; Afzal, Muhammad Babar Shahzad; Basoalto, Esteban; Raza, Abu Bakar Muhammad; Banazeer, Ansa
Abstract: Cotton mealybug Phenacoccus solenopsis Tinsley is an important pest of cotton in Pakistan, and its management is difficult due to the development of insecticide resistance. This research was conducted to characterize the bifenthrin resistance in populations of P. solenopsis and different parameters such as cross-resistance, realized heritability and possible resistance mechanisms were studied to improve the management of this important pest. A field-collected population was selected with bifenthrin in the laboratory for 14 generations and developed a resistance of 178-fold. The realized heritability of bifenthrin resistance was 0.54 in the selected population. The toxicity of bifenthrin was synergized by the addition of either piperonylbutoxide (PBO) or S, S, S tributylphosphorotrithioate (DEF) which suggests a general metabolic resistance due to possible involvement of mono-oxygenases or esterases. However, the resistant population did not develop a significant cross-resistance to either buprofezin, chlorpyrifos or lambda-cyhalothrin. These data suggest that alternative insecticide-based management programs can be developed for this pest in the short-term, but resistance management strategies which can reduce the sole reliance on insecticides are still needed. Highlights: Selection of cotton mealybug in the laboratory with bifenthrin produced a 178-fold resistant strain. The realized heritability of bifenthrin resistance was 0.54 in the selected population. Selected population showed very low cross-resistance against various insecticides. The toxicity of bifenthrin was synergized by the addition of either piperonylbutoxide or S, S, S tributylphosphorotrithioate.